Bridging the gap between planning process in municipalities and landscape architecture studies and research in Latvia - Ņitavska, Natalija; Zigmunde, Daiga; Markova, Madara; Īle, Una (Journal of Architecture and Urbanism, 2016)
This article deals with the implementation stages and approaches of the trilateral cooperation “university – student – local government” as well as the benefits and limiting aspects in a real territory planning context. The research summarises the evaluation of the Latvia University of Agriculture (LUA) landscape architecture studies experience in cooperation with 41 municipal and national organisations and 4 unions from Latvia since 2013. Key findings point to the following benefits: the university as a provider of study process obtains a better insight into the topical problems and issues regarding the territorial/territory planning, it has an opportunity to promote the study programmes and the work quality of the future specialists; the greatest benefit for the students is that they can be better prepared for a real work in their chosen profession and they gain experience in real project work which later will be reflected in their CVs; the gain for the local governments is that they have a scientific substantiation for making more appropriate decisions with regard to the further development of the territory, and they have more variants of ideas for a specific territorial development. Restricting factor is time which is determined by the study courses.